APLIKASI MEMBRAN JENIS SPIRAL-WOUND PADA PENGOLAHAN LIMBAH CAIR SEKUNDER - Subriyer Nasir (Purifikasi, 2010)
Study on secondary effluent treatment from Kwinana Water Reclamation Plant (KWRP), Western Australia, was done in small scale Reverse Osmosis (RO) system with a capacity of 2000 L/d. The RO system was equipped with two spiral wound membrane module. Effect of operating pressures and build-up of sodium and calcium ions on membrane surface were important subjects in this research. Results of this study showed that permeate flux, rejection percentage of Total Organic Carbon (TOC) and Total Dissolved Solids (TDS) were significantly affected by operating pressure. However, percentage of water recovery could be achieved only around 48% at an operating pressure of 3250 kPa.